Investigating the Challenges Faced by English Education Students in Writing Undergraduate Theses - Rizqi Elzahra, Hilda (Journal of Applied Linguistics and English Education, 2026)
This study explores the difficulties experienced by English Language Education students at Universitas Muhadi Setiabudi Brebes in writing their undergraduate theses and identifies the most dominant challenges encountered during the process. Using a qualitative case study design, data were collected through semi-structured interviews involving students who were in the process of or had completed their thesis writing. The data were analyzed thematically to identify recurring patterns of difficulties. The findings reveal that students face multidimensional challenges, including linguistic difficulties (grammar, vocabulary, and paraphrasing), academic writing and research-related difficulties (literature review development, methodology selection, organization of findings, and citation practices), psychological and affective factors (lack of confidence, anxiety, and fear of making mistakes), as well as supporting factors such as limited research experience and poor time management. Among these, academic writing and research-related difficulties, particularly in literature review development and methodology selection, emerge as the most dominant challenges. The study also shows that psychological factors significantly intensify students’ writing difficulties by reducing motivation and increasing dependence on supervisors, which in turn interacts with linguistic and academic limitations and creates a cyclical pattern of writing obstacles. Overall, the study concludes that undergraduate thesis writing is a complex, multidimensional process involving linguistic, cognitive, academic, and emotional components, requiring comprehensive support from lecturers and supervisors to help students successfully complete their theses.